Hemodynamic Response to Upper Airway Obstruction in Hypertensive and Normotensive Pregnant Women - John Reid; Riley A. Glew; Joe Mink; John Gjevre; Mark Fenton; Robert Skomro; Femi Olatunbosun (Canadian Respiratory Journal)
Background. Mild obstructive sleep apnea is common in pregnancy and may have an exacerbating role in gestational hypertension, although currently the interaction between these two diseases is uncertain. Methods. We analyzed 43 pregnant subjects, 28 with gestational hypertension (GH) and 15 with normal healthy pregnancy, by level I polysomnography. Additionally, diastolic and systolic blood pressure changes in response to obstructive respiratory events were measured by noninvasive beat-by-beat monitoring. We also assessed a subgroup (n=27) of women with respiratory disturbance indexes <5, for blood pressure responses to very subtle obstructive respiratory disturbances (“airflow reductions”). Results. The mean ± standard deviation respiratory disturbance index of our 28 GH women and 15 healthy pregnant women was 10.1±9.9 mmHg and 3.0±3.8 mmHg, respectively. Systolic and diastolic pressure responses to these events were 30.1±12.8 mmHg and 16.0±6.1 mmHg for GH women and 29.1±14.2 mmHg and 14.3±7.7 mmHg for healthy women. For the 27 women in whom we assessed for airflow reduction events, the hemodynamic responses were 27.1±12.3 mmHg systolic and 14.4±6.7 mmHg diastolic. Interpretation. Upper airway obstructive events of any severity are associated with a substantial transient blood pressure response in both healthy pregnant and GH women. Whether or not these events have a clinically significant impact on women with GH remains uncertain.